IMPROVING STUDENTS’ READING SKILL BY USING READING RACE STRATEGY TO THE EIGHT GRADE OF SMPN 1 JENANGAN - ulfa wulan agustina (Universitas KH. A. Wahab Hasbullah, 2019)
Reading is a means of language acquisition, communication, sharing information and ideas. It is a process to get knowledge through written text. Reading skill has important role to other skills, such as listening, writing and speaking skill. But, reading became a difficulty for students of SMPN 1 Jenangan especially class 8C. It is influenced by some factors among others: the students have low desire to read English text, the students read the text slowly and they get difficulty to comprehend the text. To improve the students’ reading skill, the researcher applied Reading Race strategy.Reading Race strategy is innovative strategy in teaching and learning English which helps students to be able to read the English text, comprehend it and find the idea of text fluently and easily.The design of this study was Classroom Action Research. The research was conducted in SMPN 1 Jenangan. It is located on Jalan Raya Jenangan- Kesugihan.The subject of the study were students of 8C SMPN 1 Jenangan Ponorogo.The class consist of 37 students, 20 males and 17 females. This study was conducted in May. It was conducted in 2 cycles. Technique of collecting data were questionnaire, observation, test and field note.Based on the result of the study, the achieved percentage of reading test (group) of cycle I was 69.89 % and 74.91% in cycle II. While the achieved percentage of reading test (individually) of cycle I was 67.91% and 75.64% in cycle II. Moreover, the percentage of observation on students’ activities of cycle I was 63.91% and 71.48% in cycle II. The result of questionnaire showed that students’ perception and interest in English have been improved.100% of students like Reading Race strategy, 65% of students did not get difficulty in reading an English text, 78% of students thought that English is easy, while 73% of students did not translate English text word by word, and 59% of students did not get difficulty to find out information of the text.Based on explanation above, it could be concluded that Reading Race strategy can improve students’ reading skill. Beside that, it improves students’ motivation, activities and interest in teaching learning process.